2015
DOI: 10.1039/c5cp04893a
|View full text |Cite
|
Sign up to set email alerts
|

Revealing unusual chemical bonding in planar hyper-coordinate Ni2Ge and quasi-planar Ni2Si two-dimensional crystals

Abstract: We discover unusual chemical bonding in a novel planar hyper-coordinate Ni2Ge free-standing 2D monolayer, and also in a nearly planar slightly buckled Ni2Si monolayer. This unusual bonding is revealed by Solid State Adaptive Natural Density Partitioning analysis. This analysis shows that a new type of 2c-2e Ni-Si σ and 3c-2e Ni-Ge-Ni σ bonds stabilize these 2D crystals. This is completely different from any previously known 2D crystals. Both of these free-standing monolayers are global minima in two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 47 publications
3
65
2
Order By: Relevance
“…We compared the calculated values of our new materials to that of several commonly known 2D materials, including graphene, MoS 2 , silicene, germanene, and recently predicted X 2 Y (X = Cu/Ni; Y = Si/Ge) [34][35][36] and pure transition metal monolayers. The in-plane Young's modulus, (or in-plane stiffness), is commonly used to evaluate the mechanical stability of 2D layered materials.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the calculated values of our new materials to that of several commonly known 2D materials, including graphene, MoS 2 , silicene, germanene, and recently predicted X 2 Y (X = Cu/Ni; Y = Si/Ge) [34][35][36] and pure transition metal monolayers. The in-plane Young's modulus, (or in-plane stiffness), is commonly used to evaluate the mechanical stability of 2D layered materials.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 Such new 2D materials have unusual chemical bonding and stoichiometry, which could structurally mimic graphene monolayer. [26][27][28] Black phosphorous, the thermodynamically most stable allotrope of phosphorous 29 , is a layered material like graphite and is known to possess a large theoretical capacity of 2596 mAhg − 1 . 30,31 However poor cycle life and irreversible structural change limits its application as negative electrode in LIB.…”
Section: Introductionmentioning
confidence: 99%